A simulator of human physiology under energy balance in cells - Grygoryan, R.D.; Degoda, A.G.; Dzhurinsky, E.A.; Aksenova, T.V. (Інститут програмних систем НАН України, 2019)
For IBM-compatible personal computers, a software simulator (PS) is created, based on simplified mathematical models (UMM) of complex physiological systems (CFS) that provide energy balance in human cells. The differential equations of the previously created and published dynamic model in UMM are replaced by algebraic equations describing the proportional dependences between the variables of the state of the CFS. UMMs describe only the statics of cellular and multicellular CFS. The PS developed in C ++ provides the user (physiologist) with an interface through which different combinations of specified state variables are selected to calculate the mean arterial pressure (SBP). Multidimensional equations contain coefficients characterizing the sensitivity of state variables to changes in the energy status of the organism. By means of numerical values of these coefficients the user can simulate different static physiological regimes of the organism. Examples of such computations are given. PS is a convenient information technology, complementing the traditional empirical methods of human physiology.Problems in programming 2018; 4: 93-100